2018
DOI: 10.1007/s00264-018-3984-x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of plain antero-posterior radiographic-based methods for measurement of acetabular cup version

Abstract: For measurement of acetabular cup version angle, we recommend the use of Lewinnek and Liaw et al. methods both in AP-P and in AP-H, while Hassan et al.'s method is recommended in AP-P only, and Widmer and Ackland et al.'s methods in AP-H only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…For more precise measurements, a computed tomography (CT) can be requested to assess the femoral and acetabular torsion [9]. However, this is not performed routinely and data on the rotational profile of the CT in correlation to plain radiography is lacking in the literature, especially in DDH or borderline hips [10][11][12][13][14]. Some authors have provided a comparison between the lesser trochanter size on plain radiographs to the femoral version on a CT [15], although further description is largely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…For more precise measurements, a computed tomography (CT) can be requested to assess the femoral and acetabular torsion [9]. However, this is not performed routinely and data on the rotational profile of the CT in correlation to plain radiography is lacking in the literature, especially in DDH or borderline hips [10][11][12][13][14]. Some authors have provided a comparison between the lesser trochanter size on plain radiographs to the femoral version on a CT [15], although further description is largely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, although the accuracy of OrthoView system measurements has been demonstrated, measurement bias cannot be ignored. X-ray-based postoperative measurements are inferior to computed tomography (CT) and magnetic resonance imaging (MRI); however, studies have confirmed that X-rays have the same accuracy as CT [ 35 37 ]. Fourthly, due to the relatively small sample size of our study, and the relatively small number of morbidly obese patients in China, no analysis stratified by BMI was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…12 Alzohiry et al recommend the Lewinnek et al and Liaw methods for determining the anteversion angle on anteroposterior pelvis or anteroposterior hip radiographs. 13 Figure 3 is an X-ray of a patient that sustained a right neck of femur fracture. In the Liaw method, a line is drawn across the maximal diameter of the ellipse (AB) on the anteroposterior radiograph, and another point (C) midway on the ellipse, which is the intersection of the ellipse, and a line perpendicular to and going through the midpoint of AB is determined.…”
Section: Discussionmentioning
confidence: 99%